Realizing a Source of Income for the Women's Farmers Group of Klepu Lor Hamlet, Sendangmulyo Subdistrict by Developing an Instant Lemongrass Drink Business: Mewujudkan Sumber Pendapatan Kelompok Wanita Tani Dusun Klepu Lor Kelurahan Sendangmulyo dengan Pengembangan Usaha Minuman Instan Sereh Wangi - Warmanti Mildaryani; Bambang Nugroho; Dian Astriani (Universitas Muhammadiyah Palembang, 2026)
Klepu Lor Hamlet, 14 kilometers from the center of Yogyakarta, located in Sendangmulyo Village, Minggir District, Sleman Regency, Special Region of Yogyakarta Province, has many potentials including: agriculture, animal husbandry, fisheries, culinary educational tourism, and arts and culture. Lemongrass plants are abundant in residents' yards but have not yet been utilized commercially. Based on observations, exploration, and evaluation of residents and the environment, the community needs assistance in developing an instant lemongrass drink business. The objectives of this community service program are: 1) to improve the community's ability to develop instant lemongrass beverage businesses. 2) to increase community income and welfare. The methods used are counseling and training, covering beverage product creation, packaging, business management, marketing strategies, market testing, and assistance with PIRT management. The target partner for this community service program was the Independent Women's Farmers Group in Klepu Lor hamlet. The resulting lemongrass beverage business group, labeled